2016
DOI: 10.3389/fpls.2016.01880
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Accessions with Reduced Drosophila suzukii Emergence From Fruits

Abstract: Drosophila suzukii is threatening soft fruit production worldwide due to the females’ ability to pierce through the intact skin of ripe fruits and lay eggs inside. Larval consumption and the associated microbial infection cause rapid fruit degradation, thus drastic yield and economic loss. Cultivars that limit the proliferation of flies may be ideal to counter this pest; however, they have not yet been developed or identified. To search for potential breeding material, we investigated the rate of adult D. suzu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 24 publications
(27 reference statements)
2
28
0
Order By: Relevance
“…We concluded that D. suzukii has access to strawberries at the onset of their maturation but strongly prefers blushing and ripe fruit stages. These results are consistent with previous observations that used different strawberry cultivars and other species of berry [10, 13, 14]. Together, they establish that D. suzukii , compared to other closely related species, has shifted its oviposition target from rotten to earlier stages of fruit maturation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We concluded that D. suzukii has access to strawberries at the onset of their maturation but strongly prefers blushing and ripe fruit stages. These results are consistent with previous observations that used different strawberry cultivars and other species of berry [10, 13, 14]. Together, they establish that D. suzukii , compared to other closely related species, has shifted its oviposition target from rotten to earlier stages of fruit maturation.…”
Section: Resultssupporting
confidence: 92%
“…We analyzed the oviposition behavior of D. suzukii and some close relatives using strawberries (genus Fragaria ), a main target of D. suzukii , at different stages of maturation [10]. We first compared ripe, pristine strawberries (hereafter referred to as “ripe fruit”), purchased from a local grocery store, to strawberries from a similar batch left to decay for 4 days (hereafter referred to as “rotten fruit”; see Supplemental Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, larval development and exposure to pathogens result in damage to a wide range of small and stone fruits [6,8]. To date, most research on D. suzukii has focused on adults [3][4][5][9][10][11], while little is known about larval adaptations, although the ecological niche of larvae in D. suzukii is quite unique. Our work focuses on the comparative analysis of larval behavioural and metabolic responses in the presence of nitrogenous waste and the related oviposition behaviour in adult females in D. melanogaster and D. suzukii.…”
Section: Introductionmentioning
confidence: 99%
“…The cultivars that do not support the propagation of D. suzukii have not yet been identified in the world, but their development in the future could be an effective alternative to chemical control treatments (Gong et al, 2016).…”
Section: Significance Of This Studymentioning
confidence: 99%